THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ENGLISH LANGUAGE TEACHING AND LEARNING - Urinbekova Ezozakhon Uchqunovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article examines the impact of artificial intelligence (AI) on English language teaching and learning in contemporary educational settings. It discusses the role of AI in personalizing instruction, improving language assessment, enhancing speaking, writing, reading, and vocabulary acquisition, and supporting teachers through intelligent educational technologies. The article also explores the advantages, challenges, and future prospects of AI integration in English language education. It concludes that AI serves as an effective educational tool that enhances learning outcomes while complementing, rather than replacing, the role of teachers.